Altered Glycosylation in the Aging Heart - Franzka, Patricia; Krüger, Lynn; Schurig, Mona K.; Olecka, Maja; Hoffmann, Steve; Blanchard, Véronique; Hübner, Christian A. (Frontiers in Molecular Biosciences, 2021)
Cardiovascular disease is one of the leading causes of death in developed countries. Because the incidence increases exponentially in the aging population, ageing is a major risk factor for cardiovascular disease. Cardiac hypertrophy, fibrosis and inflammation are typical hallmarks of the aged heart. The molecular mechanisms, however, are poorly understood. Because glycosylation is one of the most common protein post-translational modifications and can affect biological properties and functions of proteins, we here provide the first analysis of the cardiac glycoproteome of mice at different ages. Western blot as well as MALDI-TOF based glycome analysis suggest that high-mannose N-glycans increase with age. In agreement, we found an age-related regulation of GMPPB, the enzyme, which facilitates the supply of the sugar-donor GDP-mannose. Glycoprotein pull-downs from heart lysates of young, middle-aged and old mice in combination with quantitative mass spectrometry bolster widespread alterations of the cardiac glycoproteome. Major hits are glycoproteins related to the extracellular matrix and Ca2+-binding proteins of the endoplasmic reticulum. We propose that changes in the heart glycoproteome likely contribute to the age-related functional decline of the cardiovascular system.